Does Language Matter? Identity-First Versus Person-First Language Use in Autism Research: A Response to Vivanti - Gemma Williams (Journal of Autism and Developmental Disorders, 2021)
In response to Vivanti’s ‘Ask The Editor…’ paper [Journal of Autism and Developmental Disorders, 50(2), 691–693], we argue that the use of language in autism research has material consequences for autistic people including stigmatisation, dehumanisation, and violence. Further, that the debate in the use of person-first language versus identity-first language should centre first and foremost on the needs, autonomy, and rights of autistic people, so in to preserve their rights to self-determination. Lastly, we provide directions for future research.